2022
DOI: 10.1177/10998004211065491
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium, Potassium, and Sodium to Potassium Ratio in Patients With Systemic Lupus Erythematosus

Abstract: Purpose: The aim of this study was to investigate the association between dietary sodium, potassium, and sodium:potassium ratio and clinical disease activity parameters, damage accrual, and cardiovascular disease risk factors in a population of patients with systemic lupus erythematous (SLE). Research design and study sample: A cross-sectional study including a total of 280 patients was conducted (90.4% females; mean age 46.9 ± 12.85 years). Data collection: The SLE Disease Activity Index (SLEDAI-2K) and the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Studies on the effect of sodium in SLE are limited, but recent work has highlighted that low sodium regimen diet resulted in a reduction of Th17 percentages (p=0.001), while Tregs percentages increased, therefore suggesting a link between salt intake and autoimmunity (p=0.02) (246). One study exploring high dietary intake of sodium and low potassium intake in SLE patients found an association with an increased risk of high-sensitivity CRP (p=0.004), a marker of disease activity and cardiovascular risk, supporting the potential for sodium to adversely affect inflammation (247). High sodium was also associated with anti-dsDNA (p=0.001) and complement C4 (p=0.039), while low potassium was associated with C3 level (247).…”
Section: Sodium Potassiummentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the effect of sodium in SLE are limited, but recent work has highlighted that low sodium regimen diet resulted in a reduction of Th17 percentages (p=0.001), while Tregs percentages increased, therefore suggesting a link between salt intake and autoimmunity (p=0.02) (246). One study exploring high dietary intake of sodium and low potassium intake in SLE patients found an association with an increased risk of high-sensitivity CRP (p=0.004), a marker of disease activity and cardiovascular risk, supporting the potential for sodium to adversely affect inflammation (247). High sodium was also associated with anti-dsDNA (p=0.001) and complement C4 (p=0.039), while low potassium was associated with C3 level (247).…”
Section: Sodium Potassiummentioning
confidence: 99%
“…One study exploring high dietary intake of sodium and low potassium intake in SLE patients found an association with an increased risk of high-sensitivity CRP (p=0.004), a marker of disease activity and cardiovascular risk, supporting the potential for sodium to adversely affect inflammation (247). High sodium was also associated with anti-dsDNA (p=0.001) and complement C4 (p=0.039), while low potassium was associated with C3 level (247). These findings indicated that these disease activity biomarkers in lupus may be affected by consumption of sodium and potassium.…”
Section: Sodium Potassiummentioning
confidence: 99%
“…A high salt diet can also accelerate the development of lupus through the regulation of dendritic cell activity via MAPK and STAT1 signaling pathways [ 123 ]. Higher dietary sodium and lower dietary potassium intake were significantly correlated with C-reactive protein (CRP), which may lead to an increase in disease severity [ 124 ]. A diet rich in eicosapentaenoic acid (EPA) was found to ameliorate the lupus nephritis manifestations including immune complex accumulation and autoantibody generation in the kidney [ 125 ].…”
Section: Environmental Factorsmentioning
confidence: 99%